PENGARUH PAPARAN KADMIUM DALAM PESTISIDA TERHADAP FUNGSI KOGNITIF YANG DIUKUR DENGAN MINIMENTAL STATE EXAMINATION (MMSE) DAN MONTRAL COGNITIVE ASSESSMENT VERSI INDONESIA (MOCA-INA) PADA PETANI DUSUN CANGAR - Syukron Fadillah; Fathia Annis Pramesti; Aris Widodo (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2020)
Introduction: Farmers are a group of workers that uses pesticide evenly. The exposure of pesticide that contains cadmium (Cd) inside it in a long period of time will affect cognitive function. This research is aimed for knowing the effect of cadmium exposure on pesticide for cognitive function to the farmers at Cangar Village, Bulukerto, Bumiaji, Batu City.Method: This research uses observational analytical descriptive method with cross sectional design. it uses 47 human respondents with purposive sampling technique for sample choosing. The respondent is a male farmer that actively uses pesticide for spraying the plant. The data collection uses The Prospective Investigation of Pesticide Applicator’ Healt (PIPAH), Minimental State Examination (MMSE), and Montreal Cognitive Assessment Indonesian Version (MoCa INA) questionnaire.Result : The exposure variable gives negative effect and significant for MMSE variable with liniar regressive test significance is less than α (0.000<0.050). The determinant coefisien number is 0.0551 which shows that the exposure variable gives the negative effect and significant for MoCa-Ina variable with liniar regressive test significance is α (0.001<0.050). The determinant coefisien number is 0.212 which shows that the exposure variable gives effect for 21.2 % to MoCa-Ina variable Conclusion: The cadmium exposure in pesticide gives impact for kognitive function.Keywords: Cadmium, Pesticides, Cognitive fungtion, MMSE, MoCa-Ina, Farmers